Performance characteristics of a small poppet valve crankshaft engine in free-piston engine mode - Mohd Razali, Hanipah; M. Haziq Adham, Rosli (Universiti Malaysia Pahang, 2021)
The free-piston engine generator (FPEG) provides a novel method for electrical power generation in the range extender and hybrid electric vehicle application. In this paper, one-dimensional (1D) numerical simulations of a two-stroke poppet valve in crankshaft engine (CSE) and free-piston engine (FPE) modes are presented to illuminate the potential performance gain of a two-stroke poppet valve engine for free-piston engine generator application. The 1D numerical simulation for crankshaft and free-piston engine models focuses on the two-stroke engine performance response. Both models were subjected to variations of ignition and valve timings. The impact of lambda on engine performance was obtained. Finally, a single speed of 3000 rpm was chosen for detail performance behaviour of the free-piston engine model response. The results have shown that the CSE model has demonstrated traditional performance behaviour against ignition timing variation. In addition, FPE model performance is highly affected by both intake and exhaust valve timings as compared to the CSE model. Furthermore, CSE is superior to FPE across lambda variations for BSFC, brake thermal efficiency, brake power and bmep. These models have successfully portrayed realistic engine performance response as presented in the lambda variations simulation. When simulated at an intended operating speed of 50 Hz, the FPE model has shown poorer performance. The bmep and brake power of FPE model dropped by 3%, brake thermal efficiency dropped by 26%, and BSFC increased by 21%. This lower performance is attributed by 30% reduction in piston velocity suffers in FPE, which contributed to 13% reduction in peak cylinder pressure. Ignition delays promote better FPE performance which is able to match the CSE model. In conclusion, this paper has demonstrated the performance behaviour of a two-stroke free-piston engine model based on the baseline crankshaft engine model.